Perlindungan Hukum Laporan Transaksi Keuangan Mencurigakan Oleh Notaris dalam Prinsip Mengenali Pengguna Jasa - Aang Okta Wijaya (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
This study explores the legal responsibilities of notaries in reporting suspicious financial transactions as part of implementing the Know Your Customer (KYC) Principle. As public officials, notaries are bound by confidentiality obligations; however, in the context of anti-money laundering and counter-terrorism financing efforts, they are also required to report suspicious activities. The research applies a normative juridical approach using qualitative methods that focus on legal document analysis. The findings indicate that the notary's reporting obligation does not violate the confidentiality principle, as it is protected by law through both preventive and repressive legal safeguards. Proper implementation of the KYC Principle and due diligence allows notaries to actively contribute to financial integrity while minimizing their legal risk.